Construction and Application of College English Blended Teaching System Based on Multidata Fusion - Aiqin Pan (Discrete Dynamics in Nature and Society)
With the rapid development of educational information technology, “online and offline” hybrid teaching has become the main trend of foreign language teaching reform in colleges and universities. The blended teaching mode integrates the traditional teaching mode with modern educational technology and reconstructs the traditional college English teaching mode in the aspects of teaching object, teaching content, teaching method, teaching environment, and teaching evaluation. Based on the multisource data such as students’ learning situation, learning duration, and academic performance, this paper builds a student English learning analysis system that realizes the integration of multisource data, completes the unified processing and analysis of multisource data, and then displays it through the interface. The system helps English teachers to guide students in different degrees according to the students’ English learning situation and academic performance, so that English teachers have a clearer and more comprehensive understanding of students’ learning and living conditions and timely guide students with incorrect learning attitudes, so as to avoid students’ detours.